Studies in the history of tax law. (London [England] : HART PUBLISHING, 2021)
"These are papers from the 10th Cambridge Tax Law History Conference, which took place in July 2020. The papers fall within the following basic themes: - UK Tax administration issues - UK tax reforms in the 20th century - History of tax in the UK (Boudicca and tithes) - The UK's first double tax treaty - The 1982 Australia-US tax treaty - The legacy of colonial influence - The decline of Dutch excises - Canadian tax avoidance, and - The rise of Ireland as a financial centre."--
1. Receivers-General of Taxes John Avery Jones -- 2. An Experiment in Tax Administration: The Licensing of Dogs Chantal Stebbings -- 3. Forms and Formalities: Communicating with the Taxman Richard Thomas -- 4. The Revolt of Boudicca and the Iceni ? A Roman Tax Revolt (or Not)? Jane Frecknall-Hughes -- 5. The Impact of the Two World Wars on the United Kingdom's Tax Law John HN Pearce -- 6. Hole and Plug Philip Ridd -- 7. The Lead Ore Tithe in Derbyshire in the 16th to 18th Centuries Barbara Abraham -- 8. 1988 and All That: Creation of UK Capital Gains Tax ? What Came After David Collison -- 9. The 1926 Double Income Tax Agreement between Great Britain and the Irish Free State Sunita Jogarajan -- 10. The Negotiation and Drafting of the 1982 Australia-United States Taxation Treaty John Taylor -- 11. 'An Embarrassing Precedent': The British India-Mysore Double Tax Arrangement of 1919 Chris Jenkins -- 12. The Colonial Taxation Policy, Income Tax and the Modern Japanese Empire Shunsuke Nakaoka -- 13. The Taxation of Maori Land Ownership in New Zealand, 1878-1952 Shelley Griffiths -- 14. The Colonial Income Tax Model (1922) and the Lessons We Can Learn: Cyprus a Specific Example Demis Ioannou -- 15. From the Core to the Fringe of the Dutch Tax System: Excises in 19th Century Henk Vording -- 16. Tax Avoidance in Canada during the Pre-Stubart Period Robert Raizenne and Colin Campbell -- 17. The Origins and Development of Ireland's Low Corporate Tax Regime Charles Garavan.
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Keywords: Taxation & duties law; Electronic books